ANALISIS PENJADWALAN PROYEK UNTUK MENGOPTIMALKAN WAKTU DAN BIAYA PENYELESAIAN PADA PT. DIMENSI ARSITEKTUR INDONESIA - Pristiana, Ulfi; Narowi, Moch. (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2016)
One of the constraints experienced in the implementation of the project company is discrepancy between the schedule of the project implementation plan withthe state of the field, causing a delay in its completion, so the effect on the cost of theproject increased. This research was conducted by taking data time shedule of PT.Dimensi Arsitektur Indonesia has undertaken the maintenance and painting of TuguPahlawan Surabaya. From these data it can be calculated by using the critical pathCPM (Crithical Path Method) and software programs. On the use of CPM (CrithicalPath Method) stages of completion which is preparing an action plan, arrange network,determine the forward and backward calculation, determining the spare time ofcalculation. The project which is the object of the study authors is the maintenance andpainting of Tugu Pahlawan Surabaya that has been done by PT. ArchitecturalDimensions Indonesia. PT. Architectural Dimensions Indonesia is a consulting servicescompany serving residential, lanscaping and interior but also engaged in the drainageand road sector. In the drafting of planning time and costs during the company onlyrelied on the experience of work done on the previous project. From the planning thathas been done by the company, then do research to find out whether the plans made thecompany so far has been optimal. The research method using descriptive researchwhere data collected by the researchers by means of direct observation of companiesand interviews, then from the data obtained researchers performed data processing andanalysis, so as to obtain an overview of the planning time and costs that may beconsidered by companies as well as can be to be completed by the company. Based onthe results of research and calculations by network planning using CPM (crithical pathmethod), it can be concluded that the planning time and cost network planning to use itby using critical path method CPM appropriate to be applied in the company at thetime of planning and project cost, because it optimizes the time and cost of the project.More efficient project time 6 days or by 9.67% and the cost of the project is alsoefficient Rp 17,709,597.6 or equal to 9.67%.Keywords: Project Scheduling, CPM, Optimization